The learning organization and his contributions for the organizational change - Solf-Zárate, Arturo (2007)
In this article the author begins by discussing the similarity and differences between individual learning, and organizational system learning from a behavioral standpoint as an introduction to the analysis of Learning Organization, an ideal type of organization that focuses on the learning of each of its members and of the whole system. The article then presents a diagnosis and elaboration of a Learning Organization using the Dimensions of the Learning Organization Questionnaire (DLOQ), an instrument developed by Watkins and Marsick (1998) aimed at measuring the Learning Culture. This instrument can be applied in any other approach of organizational change